2017
DOI: 10.18471/rbe.v31i2.16814
|View full text |Cite
|
Sign up to set email alerts
|

Temática Segurança Do Paciente Nas Matrizes Curriculares De Escolas De Graduação Em Enfermagem E Obstetrícia

Abstract: <p>Objetivos: categorizar a temática segurança do paciente nas matrizes curriculares de cursos de graduação em enfermagem e obstetrícia. Método: Estudo documental, desenvolvido em nove universidades no período de junho de 2013 a março de 2014. Foram elencadas 16 palavras-chave diretas e 12 indiretas e categorizadas conforme o <em>Patient safety curriculum guide: multi-professional edition</em>.  Resultados: As palavras-chave diretas e indiretas foram encontradas em 168 disciplinas, sendo Segu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…[6][7] In a documentary study on the PP of Nursing courses, the authors pointed out the importance of these topics, referring to them as frequent in the programmatic contents and highlighting their need to be articulated throughout the course and with other disciplines that make up the PP. 12 The results revealed that Patient Safety content has been addressed since the first period of the course, and students have contact with them throughout their entire training. Studies emphasize the importance of training nurses competent at Patient Safety, stressing the need for these aspects to be taught from the beginning of the course and seen as a continuous procedure throughout the training process.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[6][7] In a documentary study on the PP of Nursing courses, the authors pointed out the importance of these topics, referring to them as frequent in the programmatic contents and highlighting their need to be articulated throughout the course and with other disciplines that make up the PP. 12 The results revealed that Patient Safety content has been addressed since the first period of the course, and students have contact with them throughout their entire training. Studies emphasize the importance of training nurses competent at Patient Safety, stressing the need for these aspects to be taught from the beginning of the course and seen as a continuous procedure throughout the training process.…”
Section: Discussionmentioning
confidence: 98%
“…A large part of contents is taught by professionals, and similar data were found in a documentary study that analyzed the curricula of Nursing schools in the city of São Paulo. 12 Despite existing information on the subject, there was no discussion to change the PP regarding Patient Safety in the school researched. However, it is understood that this is a fundamental step to comply with Resolution 569/2017, which reinforces that the knowledge and practices nuclei consider this theme in their program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um estudo com objetivo de identificar o conhecimento da equipe de enfermagem acerca da segurança do paciente relacionada ao bundle de prevenção da PAV, aborda à necessidade de conhecimento especifico do profissional para atender a essa demanda de cuidados peculiares 40 . A fragilidade no conhecimento sobre prevenção da PAV remete a necessidade de inclusão do tema segurança do paciente ao longo de todo o processo de formação dos profissionais, sendo essencial a revisão dos projetos político pedagógicos dos cursos de graduação em saúde, bem como a implementação de estratégias que possibilitem o alinhamento desse tema junto às demais disciplinas da área de saúde 41,42 .…”
Section: Discussionunclassified
“…There is, in the Brazilian health and education spaces (1) , an increasing effort and commitment to Patient Safety (PS) (2)(3) , especially in view of the creation of the Brazilian National Patient Safety Program (Programa Nacional de Segurança do Paciente) (2) . Collaborative partnership with the family is among the challenges (2)(3)(4) , with a differentiated emphasis on child hospitalizations (4) .…”
Section: Introductionmentioning
confidence: 99%